2017
DOI: 10.5604/16652681.1231585
|View full text |Cite
|
Sign up to set email alerts
|

Combination of TACE and Sorafenib Improves Outcomes in BCLC Stages B/C of Hepatocellular Carcinoma: A Single Centre Experience

Abstract: This retrospective analysis showed the use of sorafenib in patients selected according to BCLC staging, and it is the first external validation of early dermatologic adverse events as a predictor of overall survival in patients with advanced hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 22 publications
3
18
2
Order By: Relevance
“…The adverse reactions reported with high frequency in this study agree with data reported in the literature [7,11,18,21,22]. Diarrhea was described as an adverse reaction relative to a better response to treatment with SOR [10,21]. Howell et al [21] demonstrated an association of diarrhea with increased overall survival in patients treated with SOR, and other studies suggest that the occurrence of hand-foot skin reaction is a good prognostic feature [10,13,18,21].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The adverse reactions reported with high frequency in this study agree with data reported in the literature [7,11,18,21,22]. Diarrhea was described as an adverse reaction relative to a better response to treatment with SOR [10,21]. Howell et al [21] demonstrated an association of diarrhea with increased overall survival in patients treated with SOR, and other studies suggest that the occurrence of hand-foot skin reaction is a good prognostic feature [10,13,18,21].…”
Section: Discussionsupporting
confidence: 80%
“…This beneficial effect of SOR on survival has also been reported in the Asia Pacific trial [12]. Corroborating our results, another Brazilian retrospective analysis of patients treated with SOR in real-life clinical conditions demonstrated a median overall survival of 19.9 months [10]. However, overall survival in our cohort was higher than previously reported.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations